PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA IPAS MATERI INDONESIAKU KAYA BUDAYA KELAS IV SD - Nadila Salsabila; Rapita Silalahi, Beta; Hasanah; Muhammad Noer Fadlan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interactive learning media based on Articulate Storyline 3 in the Science subject of My Indonesia is Rich in Culture for grade IV elementary school with the ADDIE development model consisting of 4 stages, namely Analysis, Design, Development, and Implementation. It can be concluded that the results of the validation of material experts obtained a percentage of 77% with good criteria and were stated to be usable without revision. The results of the validation of media experts obtained a percentage of 83% with very good criteria and could be used without revision. The results of teacher responses to the developed media obtained a percentage of 94% with very practical criteria and could be used without revision. The results of student responses based on a questionnaire on learning interest using the Articulate Storyline 3 learning media in the Science subject of My Indonesia is Rich in Culture given to all 17 students obtained a percentage of 94% with very strong interest criteria. The interactive learning media based on Articulate Storyline 3 developed in the Science subject of My Indonesia is Rich in Culture is ready to be implemented as a learning media in schools. This is because the developed media has been declared very good or very feasible.